Large‐Amplitude Oscillatory Motion of Mercury's Cross‐Tail Current Sheet. Issue 7 (13th July 2020) - Poh, Gangkai; Sun, Weijie; Clink, Kellyn M.; Slavin, James A.; Dewey, Ryan M.; Jia, Xianzhe; Raines, Jim M.; DiBraccio, Gina A.; Espley, Jared R.
Abstract: We surveyed 4 years of MESSENGER magnetic field data and analyzed intervals with observations of large‐amplitude oscillatory motions of Mercury's cross‐tail current sheet, or flapping waves, characterized by a decrease in magnetic field intensity and multiple reversals of B X, oscillating with a period on the order of ~4 – 25 seconds. We performed minimum variance analysis (MVA) on each flapping wave event to determine the current sheet normal. Statistical results showed that the flapping motion of the current sheet caused it to warp and tilt in the y ‐ z plane, which suggests that these flapping waves are kink‐type waves propagating in the cross‐tail direction of Mercury's magnetotail. The occurrence of flapping waves shows a strong preference in Mercury's duskside plasma sheet. We compared our results with the magnetic double‐gradient instability model and examined possible flapping wave excitation mechanism theories from internal (e.g., finite gyroradius effects of planetary sodium ions Na + on magnetosonic waves) and external (e.g., solar wind variations and K‐H waves) sources. Key Points: Large‐amplitude oscillations of Mercury's cross‐tail current sheet (or flapping waves) with period of ~4 – 25 s were observed Flapping motion of Mercury's cross‐tail current sheet warped and tilted the current sheet in the y ‐ z plane Flapping waves preferentially occur in Mercury's duskside current sheet